تأثير العوامل الانوائية في إحساس الانسان العراقي - نعمة محسن لفتة; جاسم حميد كاظم (PROSPECTIVE RESEARCHES, 2023)
29 Iraqi stations data were used to evaluate and calculate the temperature humidity index (THI) and the wind cooling index (K). 14 stations used for statistical climatical tables due to the stability for long period range, while all the station used in drawing the maps. We obtained results with high values corresponding to standard international values, these values interest people working in industrial tourism, environmental and climatologist.